Insights Into the Microstructure and Dielectric Properties of Cold Sintered NaCa2Mg2V3O12 Based Composites - Madhuri, Rakhi; Narayana Iyer, Santha; Ganesanpotti, Subodh (Frontiers in Materials, 2021)
Cold sintering process was successfully employed to fabricate (1-x) NaCa2Mg2V3O12 –xNaCl (abbreviated as (1-x) NCMVO-xNaCl) microwave dielectric ceramics. (1-x)NCMVO-xNaCl ceramics prepared at 200°C and at a pressure of 450 MPa had a high relative density of 80–94%. X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and Raman spectroscopy showed that both NCMVO and NaCl phases co-exist in all composite ceramics without forming any secondary phase. Further, dependence of microstructure and dielectric properties on cold sintering temperature and duration were investigated in detail and their optimised values to obtain maximum density of ceramic composites were 200 oC and 50 min respectively. (1-x)NCMVO-xNaCl (x=0.4 to 0.7)) composites have relative permittivity (εr) in the range of 6.9 to 7.4, and a reasonably high microwave quality factor (Q × f) of 5000 to 13830 GHz.